Opportunistic infections in a renal transplant recipient - Vijaya V. Mysorekar; Mahesh Eshwarappa; Umesh Lingaraj (MDPI AG, 2012)
With the present progress in transplantation procedures, there is an improvement in patient and allograft survival. However, the immunosuppression necessary to sustain the allograft predisposes these transplant recipients to infection, which is now a significant cause of morbidity and mortality. We describe a case of a 30-year-old renal transplant recipient with two opportunistic infections, namely, primary cutaneous aspergillosis and intestinal tuberculosis, with terminal enterococcal pleuritis and peritonitis. Control of the degree of immunosuppression, and prompt recognition and treatment of infection are vital for successful organ transplantation.